Comparative In Vitro Study of Cinnamon (Cinnamomum burmannii) Extract and Ciprofloxacin on the Inhibition of Escherichia coli Growth Causing Urinary Tract Infection - Milala, Alvin Nugraha S.; Nasution, Sri Wahyuni; Rusip, Gusbakti (Fakultas Kedokteran Universitas Malikussaleh, 2025)
Cinnamon (Cinnamomum burmannii) contains various bioactive compounds, primarily cinnamaldehyde and eugenol, which are known for their antibacterial properties. The increasing resistance of Escherichia coli to conventional antibiotics highlights the need for developing effective natural alternatives with antimicrobial potential.This study aimed to determine the antibacterial effectiveness of cinnamon extract compared to ciprofloxacin in inhibiting the growth of Escherichia coli.This research was an experimental laboratory study using the disc diffusion method to measure antibacterial activity.The results showed that cinnamon extract was capable of inhibiting Escherichia coli growth, with mean inhibition zone diameters of 11.84 mm at 25%, 13.94 mm at 50%, 17.52 mm at 75%, and 15.79 mm at 100% concentrations. In comparison, ciprofloxacin produced an inhibition zone of 18.37 mm, aquadest showed no inhibitory effect.Cinnamon extract demonstrated antibacterial activity against Escherichia coli, with the highest effectiveness observed at a concentration of 75%, although its inhibitory power remained lower than that of ciprofloxacin.